2001
DOI: 10.1093/nar/29.13.2795
|View full text |Cite
|
Sign up to set email alerts
|

Hexamminecobalt(III)-induced condensation of calf thymus DNA: circular dichroism and hydration measurements

Abstract: The interaction of hexamminecobalt(III), Co(NH(3))(6)(3+), with 160 and 3000-8000 bp length calf thymus DNA has been investigated by circular dichroism, acoustic and densimetric techniques. The acoustic titration curves of 160 bp DNA revealed three stages of interaction: (i) Co(NH(3))(6)(3+) binding up to the molar ratio [Co(NH(3))(6)(3+)]/[P] = 0.25, prior to DNA condensation; (ii) a condensation process between [Co(NH(3))(6)(3+)]/[P] = 0.25 and 0.30; and (iii) precipitation after [Co(NH(3))(6)(3+)]/[P] = 0.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
96
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(111 citation statements)
references
References 61 publications
13
96
2
Order By: Relevance
“…43,44) It is similar to that observed for [Ru(NH 3 ) 4 (qdppz)] 2ϩ and [Co(NH 3 ) 6 ] 3ϩ bound to DNA of short lengths with 160 base pairs. 45,46) The results obtained here validate those obtained from the UV-Vis spectral studies.…”
Section: )supporting
confidence: 84%
See 1 more Smart Citation
“…43,44) It is similar to that observed for [Ru(NH 3 ) 4 (qdppz)] 2ϩ and [Co(NH 3 ) 6 ] 3ϩ bound to DNA of short lengths with 160 base pairs. 45,46) The results obtained here validate those obtained from the UV-Vis spectral studies.…”
Section: )supporting
confidence: 84%
“…43,44) It is similar to that observed for [Ru(NH 3 ) 4 (qdppz)] 2ϩ and [Co(NH 3 ) 6 ] 3ϩ bound to DNA of short lengths with 160 base pairs. 45,46) The results obtained here validate those obtained from the UV-Vis spectral studies.Viscosity Studies Hydrodynamic measurements that are sensitive to the length change (i.e., viscosity and sedimentation) are regarded as the least ambiguous and the most critical tests of a binding model in solution in the absence of crystallographic structural data. …”
supporting
confidence: 84%
“…Indeed, pure DNA when hydrated at 75% relative humidity exhibits the same behavior with a major band at 860 cm Ϫ1 and a weak band at 836 cm Ϫ1 (74). From ultrasonic and densimetric measurements, it has been found that cobalt(III)hexamine reduce the hydration of the atomic group of DNA (79).…”
Section: Effect Of Biogenic Polyamines and Cobalt(iii)hexamine On Conmentioning
confidence: 89%
“…Their deprotonation constants are: K1 = 10 -2.35 and K2 = 10 -9.87 (glycine hydrochloride), K1 = 10 -4. 16 and K2 = 10 -5.61 (succinic acid). 19 Note that a relatively low variability occurred even at high initial concentrations of the reagents.…”
Section: Resultsmentioning
confidence: 99%
“…Acoustic titration-like experiments were also made in order to characterize the acid-induced denaturation of staphylococcal nuclease at different urea concentrations, 13 to study the binding of the cationic surfactant dodecyltrimethylammonium bromide to short fragments of DNA in dilute solutions at 1 mM NaCl, 14 to analyze the binding of alamethicin to unilamellar DMPC vesicles, 15 and also to study interactions of Co(NH3)6 3+ with calf thymus DNA 16 and Cs + and Mg 2+ with polynucleotides. 17 All of the above listed reports encouraged us to test if sound speed or density measurements can be applied for monitoring simple reactions, like acid-base titration, and how to describe the observed changes.…”
Section: Introductionmentioning
confidence: 99%